Oil palm production: Actors, roles and activities in the value chain - Ngwangkfu, Yolar; Enwgali, Fon; Lengha, Tohnain (American Journal of Agriculture, 2021)
Purpose: Oil palm is the highest oil producing plant, with an average yield of 3.5 tons of oil/ha/year. In 2006, palm oil became the world's most important edible oil with 37 million tons produced, accounting for 25% of the total oils and fats production. The study on the Oil palm production: Actors, roles and activities was conducted in the Littoral region of Cameroon with the used of multi-stage sampling technique. Methodology: The target population for this study were smallholder growers/processors and marketers involved in the oil palm value chain and the sample size was four hundred (400) assuming that the growers/processors and marketers in the Littoral region are more than 100000 distributed within two divisions. The study made used of primary and secondary data sources. The methods used for the study were interviews, focus group discussions, sources documents analysis and participatory observation. A simple descriptive statistical method was also used for the study. Findings: Findings indicated that the main actors identified in the field were the input suppliers, nurseries, growers/processors, marketers and consumers. Recommendation(s): The study therefore recommends that the state through the local authorities such as the council could set up fixed prices for oil palm products, create farm to markets roads, and provide farmers with quality seedlings and fertilizers. And also growers should constitute themselves in to common initiatives groups and cooperatives.